Local fishing influences coral reef fish behavior inside protected areas of the Indo-Pacific. (February 2015) - Januchowski-Hartley, Fraser A.; Graham, Nicholas A.J.; Cinner, Joshua E.; Russ, Garry R.
Highlights: We assessed anti-predator behavior in two fishery target families in 4 countries. Flight initiation distance (FID) was examined across a fishing pressure gradient. FID increased with fishing pressure both inside and outside marine reserves. Fish size only influenced FID in fished areas and not in reserves. Local fishing pressure and buffer zones should be considered in reserve design. Abstract: Fishing is altering aquatic ecosystems through changes in the abundance, species composition and behavior of target species. Changes in fish behavior have received relatively little attention, despite significant evidence of behavioral change driven by human impacts mediating function and processes in terrestrial ecosystems, and emerging evidence that the same is true in marine systems even within marine reserves. Here, we measured the wariness of two families of coral reef fishes in both fished areas and marine reserves embedded within a fished seascape along an exploitation gradient ranging from wilderness sites (Chagos) to heavily fished areas (the Philippines). We used linear mixed effect models to identify relationships between fish flight initiation distance (FID) and fishing pressure, fish size, habitat complexity and life-history stage. Critically, fish FID increased with fishing pressure both in fished areas and inside marine reserves. These results imply that as fishing pressure increases in adjacent areas, progressively greater fish wariness may reduce the magnitude of some ecosystem functions within small marine reserves.